5 Association between combat-related traumatic injury and skeletal health: bone mineral density loss is localised and correlates with altered loading in amputees – the ADVANCE study. Issue 2 (23rd March 2023) - McMenemy, L; Behan, FP; Kaufmann, J; Cain, D; Bennett, AN; Boos, C; Fear, NT; Cullinan, P; Bull, AMJ; Phillips, ATM; McGregor, AH
Abstract : Introduction: The association between combat-related traumatic injury (CRTI) and bone health is uncertain. A disproportionate number of lower limb amputees from the Afghanistan conflict are diagnosed with osteopenia/osteoporosis, increasing lifetime risk of fragility fracture and challenging traditional osteoporosis treatment paradigms. It was hypothesised that CRTI results in a reduction in Bone Mineral Density (BMD). Specifically, a localised BMD reduction in the amputated limb of lower limb amputees that is progressively greater with higher level amputations. Method: Cross-sectional analysis of the first phase of a cohort study comprising 579 male adult UK military personnel with CRTI (UK-Afghanistan War 2003–2014; including 153 lower limb amputees) who were frequency-matched to 565 uninjured men by age, service, rank, regiment, deployment period, and role-in-theatre. BMD was assessed using DEXA scanning of the hips and lumbar spine. Results: Femoral neck BMD was lower in the CRTI than the uninjured group (T-score -0.08 vs -0.42 p=0.000). Subgroup analysis revealed this reduction was significant only at the femoral neck of the amputated limb of amputees (p=0.000), where the reduction was greater for above knee amputees than below knee amputees (p=0.037). There were no differences in spine BMD. Conclusion: Changes in bone health in CRTI appear to be mechanically driven rather than systemic. This may arise from altered joint and muscle loading creating a reduced mechanical stimulus to the femur. These findings support a lexicon change to unloading osteopenia and should not be associated with a diagnosis of systemic osteoporosis nor systemic treatments.